A study on the development of happiness scale for Chinese young children - Xiang, Jiaxin; Choi, Jieun (Frontiers in Psychology, 2024)
This study was conducted to develop an assessment tool for measuring happiness among Chinese preschoolers, and to verify the reliability and validity of this tool. A total of 269 preschoolers aged 3 to 5 years from kindergartens and childcare centers in Hangzhou, China, were surveyed. The Preschooler Happiness Scale, constructed through literature review and interviews with preschoolers, underwent expert content validity verification and pilot testing to refine items. The validity and reliability of the scale were verified in this study, resulting in the development of the final Preschooler Happiness Scale comprising 6 sub-factors and 25 items. The reliability verification revealed a high overall reliability of 0.91 for the Preschooler Happiness Scale, confirming its trustworthiness as a tool. The academic significance of the findings and the practical utility of the Preschooler Happiness Scale in early childhood education settings in China were discussed based on the results of this study.